PENGARUH KOMITMEN ORGANISASI, STRESS KERJA DAN CAREER GROWTH TERHADAP INTENSI TURNOVER KARYAWAN (STUDI KASUS PADA PT. KINI JAYA INDAH) - Mila Rahmawati; Susanti Wahyuningsih (STIE Pelita Nusantara Semarang, 2018)
This study aims to determine whether organizational commitment, job stress and career growth affect the intention of employee turnover at PT. Kini Jaya Indah and analyze the most dominant factors and affect the intention of employee turnover at PT. Kini Jaya Indah. Population in this research is employees at PT. Kini Jaya Indah. Samples taken as many as 73 respondents by using strata sampling technique, namely the collection of sample members of the population that has the characteristics that there is a division of population into several classes, categories or groups.Based on research indicate that: there is no influence of organizational commitment to employee turnover intention, there is positive influence of work stress to employee turnover intention, there is no influence growth career to employee turnover intention, coefficient of determination equal to 0,541 or 54,1% indicating that between organizational commitment (X1), work stress (X2) and career growth (X3) can simultaneously explain employee turnover intention (Y) in PT. Kini Jaya Indah is 54.1%, while the rest 45.9% is influenced by other variables that are not examined.